The Effect of Gadgets on the Learning Achievement of Elementary School-Age Children in Kejapanan Gempol Village : Pengaruh Gadget terhadap Prestasi Belajar PAI Anak Usia SD di Desa Kejapanan Gempol - Meilany, Devany Rizky Fulan; Fauji, Imam (Wadah Inovasi Indonesia, 2024)
This study aims to determine the influence of gadgets on the learning achievements of elementary school children in Kejapanan Gempol village.This researcher focuses more on elementary school children aged 6 to 11 years in Kejapanan Gempol Village, using a population of 20 children.This research will explore the relationship between gadget use and PAI learning achievement in elementary school age children. The hypothesis proposed by researchers is that there is a positive relationship between the influence of gadgets and the learning achievement of elementary school age children. The quantitative method was chosen by the researcher to achieve the objectives of this research which involved elementary school aged children in Kejapanan Gempol Village with a population and sample of 20 children. This research uses a scale of the influence of gadgets and the learning achievements of elementary school age children. The results of the product moment analysis obtained an rxy correlation coefficient value of 1.000 with a significance of 0.001 (P<0.05), meaning that there is a significant positive relationship between the influence of gadgets and the learning achievement of elementary school age children in the village of Kejapanan Gempol.